The Centenary of the Brazilian Hydrographic Service - Barreto, Mário Rodrigues (The International Hydrographic Review, 2015)
The “Repartição Hidrográfica” of the Ministry of Marine of Brazil was founded on 2nd February 1876 with the principal task of systematically surveying the coasts of Brazil. In 1976 Brazil celebrates the Centenary of the Repartição, which is now actually called the Directorate of Hydrography and Navigation. This article will show how the Coast has been surveyed over these 100 years. It will call to mind the names of those who worked for the creation of a specialised hydrographic service in the Brazilian Navy and those whose dedication has made of the Naval Hydrographic Service one of the best cartographic organisations in the country.